Tekst do słuchania (?), czyli uwagi o „muzyczności" dramatu Partita na instrument drewniany Stanisława Grochowiaka - Reimann, Aleksandra (Wydawnictwo Naukowe UAM, 2007)
The present article discusses the phenomenon of correspondence art in the drama of Stanisław Grochowiak. The title "A partita for a wooden instrument" is connected with musie. Therefore, it is interdisciplinary. The main question concerns the fact how musie can exist in the area of literature and how relations between the art of sounds and words influence each other.
A listening (?): some remarks about "musicality" of "Partita na instrument drewniany" drama ("A partita for a wooden instrument") by Stanisław Grochowiak